Khanqah Masa Sultan Nasir Muhammad Ibn Qalawun: Sejarah Berdiri dan Berkembangnya Lembaga Pendidikan Sufi Masa Mamluk Mesir - Nurrohim Nurrohim (Jurnal Tamaddun : Jurnal Sejarah dan Kebudayaan Islam, 2021)
Khanqah which is an important part in the discussion of Islamic History and Islamic Cultural History has not received sufficient portion by researchers in that field. the existence of Khanqah as an educational institution of Sufism in its time has experienced several phases of development. This is evidenced by several differences in naming the institution, such as takiyat, ribat, zawiyat, khanaqah and madrasa in the later period. This research is focused on how the development of khanqah during the reign of Sultan Nasr Muhammad ibn Qalawun, one of the sultans during the Mamluk Bahri Dynasty in Cairo, Egypt around the 14th century AD The research was then complemented by the role of Sultan Nasr and the management and administration regarding the existence khanqah and how the reactions that arise, both from among scholars and the general public. This qualitative research that uses a multidimensional approach produces several facts, namely the active role of Sultan Nasr by providing massive subsidies to both shaykh and shaykh suyukh who are specifically appointed as imams / leaders in each khanqah. In addition, the state also made a large contribution to the Sufi practitioners in the khanqah. the existence of khanqah then caused various reactions such as Ibn Jauzi, Ibn Taimiyah and al-Turkumani who often claimed that this institution was an institution containing lazy people who only hoped for the state. Another reaction is in the positive form of the existence of this institution with the development of the world of education in Islam which began with the Sufi teaching movement in the Mamluk Bahri period.Keywords: khanqah, Nasr Muhammad, Mamluk Bahri